Ops! Cabe ou não cabe? : tipologia e funcionalidade das habitações do PAR em Maceió - Porangaba, Alexsandro Tenório (2011)
The demand for social housing (HIS) has grown significantly while the internal spaces of these houses have suffered substantial reductions in size, directly affecting the use of the dwelling. In this context, the Residential Leasing Program (PAR) is notable for promoting the construction of dwellings for populations with low purchasing power, differentiated into two construction patterns: PAR-1 and PAR-2. Builders should follow the minimum building codes for construction, furnishings, equipment, living space and low-cost construction, the latter being the most relevant item in the approval of architectural proposals. Ignoring these norms, the designs of the PAR, limited to economic conditions, may manifest problems related to lack of kinesthetic space in the housing in the housing unit, incompatibility between the minimum codes and finished space and difficulty in performing domestic activities. As such, the objective of this thesis in Architecture and Urban Planning was to identify building types and analyze the functional quality of vertical housing of the Residential Leasing Program (PAR) in Maceió-AL, through the existing relationship between architectural design and furnishings with a focus on the graphical analysis of the project. Identified are the types and topological relations existing in the architectural designs of the PAR, analyzed are projects in their dimensional aspects according to the Klein Graphic Method, the composition of furniture and equipment in relation to the minimum specifications of the Caixa; spacial use of furniture and equipment in the housing based on the minimum specifications of both the Caixa and using the Design Methodology approach, developed by Boueri. PAR buildings are classified into three types: H-shaped , central core as well as stairwell and external circulation. The topological analysis showed that in eleven projects of Type 01 internal hallways connected two or three bedrooms as well as service areas.Whereas in Types 02 and 03, the living room is the principal habitation, area, functioning as a distribution point to other areas of the home. The results of the functional analysis revealed the existence of four buildings whose area is below the minimum recommended by the Caixa. The analysis carried out with regards to furniture and equipment demonstrates that the areas most inadequate, in terms of dimension and organization, are the bedrooms, living rooms and dining rooms. Analyses of living spaces and activity showed that the most adequate rooms were the kitchens and service areas. Bathrooms were, however, the most critical, especially when used by the elderly, people with temporary illness or with mobility restrictions. The functional problems identified in this thesis could have been avoided before the construction of housing units were Caixa to have made a more precise analysis of the compatibility between the design and specifications of the minimum PAR.